Mesenchymal Stem Cells Alleviate Moderate-to-Severe Psoriasis by Reducing the Production of Type I Interferon (IFN-I) by Plasmacytoid Dendritic Cells (pDCs). (7th November 2019) - Chen, Maosheng; Peng, Jing; Xie, Qi; Xiao, Na; Su, Xian; Mei, Hua; Lu, Yeping; Zhou, Jia; Dai, Yanni; Wang, Siqi; Li, Chuang; Lin, Ge; et al.
Abstract : The anti-inflammatory and immunomodulatory properties of mesenchymal stem cells (MSCs) have been proposed to be involved in some autoimmune diseases and have been successfully tested in patients and mice. But their contribution to psoriasis and the underlying mechanisms involved remains elusive. Here, we explored the feasibility of using human umbilical cord-derived MSC (hUC-MSC) infusion as a therapeutic approach in an imiquimod- (IMQ-) induced psoriasis mouse model. MSC infusion were found to significantly reduce the severity and development of psoriasis, inhibit the infiltration of immune cells to the skin, and downregulate the expression of several proinflammatory cytokines and chemokines. Our results provide an explanation for the therapeutic effects of MSC infusion by first suppressing neutrophil function and then downregulating the production of type I interferon (IFN-I) by plasmacytoid dendritic cells (pDCs). Therefore, we discovered a novel mechanism of stem cell therapy for psoriasis. In summary, our results showed that MSC infusion could be an effective and safe treatment for psoriasis.